Structure determination of N-phenylcarbazole from semi-empirical 88) Inorg, quantum chemical calculations. Extent of twisting between the carbazole hn, 0. and and phenyl moieties - Mohd Zain, Sharifuddin (Malaysian Journal of Science, 1996)
The geometrical structures of N-Phenylcarbazole (NPC) have been determined using various semi-empirical quanÂtum chemical methods. Optimizations of these structures were carÂried out using MNDO, MINDO/3, AM1 and PM3 Hamiltonians. The geometry of the predicted structures is discussed in terms of the extent of twisting of the two aryl moieties and where possible, the calculated results are compared with data obtained from superÂsonic jet studies and crystal analysis of NPC.